Drug Therapies for COPD: A Bibliometric Review From 1980 to 2021 - Zhen, Gao; Yingying, Liu; Jingcheng, Dong (Frontiers in Pharmacology, 2022)
Objective: To analyze all chronic obstructive pulmonary disease (COPD) drugs-related articles that were indexed in the Web of Science Core Collection (WOSCC) database until August 28, 2021 using bibliometric analysis, in order to provide a reliable reference for the treatment of COPD. Methods: A comprehensive search was conducted to analyze all COPD drugs-related articles using WOSCC database from inception to August 28, 2021. Abstracts and potentially eligible articles, which were retrieved during literature search, were screened by two reviewers. Besides, the CiteSpace (5.8.R1) software was utilized to analyze the overall structure of the network, the network clusters, the links between clusters, the key nodes or pivot points, and the pathways. Results: A total of 2552 COPD-drugs related articles were retrieved. From the perspective of categorization of published articles based on country, the USA is the country with the largest number of published articles and completed clinical trials, highlighting the important role of this country in the treatment of COPD. However, in terms of the proportion of ongoing clinical trials, China has the highest proportion, suggesting that China will play a more pivotal role in the medication of COPD in the future. From the perspective of cooperation among countries, the cooperation among European countries was closer than that among Asian countries. In the recent three decades, the top 20 institutions, with a particular concentration on the treatment of COPD, were from North America and Europe. The co-citation analysis showed that, among 2552 articles, 53154 citations were recorded, and the co-citation network indicated that 24 clusters could be achieved. Conclusion: The administration of bronchodilators and pulmonary drug delivery systems, as well as consideration of elderly COPD patients remained the hotspots, while triple therapy and comorbidity of COPD, as well as the prevention and treatment of elderly COPD patients had been frontiers in recent years.